Comparing Social Service's Networks for Underage Drug Users: A Cross-National Comparative Study between Malmö and Genoa - Matteo Di Placido (Social Work and Society)
Aim of this study is to describe social workers' perceptions of the influence of organizational, legal and, socio-cultural factors on their relationships with underage drug users and their families in Malmö, Sweden, and Genoa, Italy. Methodologically the study is a cross-national qualitative research. The empirics are primarily based on unstructured interviews to social workers employed in the public sector and key experts in field of drug use and drug treatment. The results of this study show the coexistence of both homogeneous and heterogeneous characteristics among the perceptions of the social workers employed by the municipalities of Malmö and Genoa, yet with a marked propensity toward diversity. In conclusion it could be stated that, among the areas of comparison discussed in this article, the organizational structure of the social services is the most prominent in influencing social workers' perceptions. In fact it further emerges that the organizational structure influences the role and the practices, the perceived social workers' satisfaction and finally the labeling consequences of underage's institutional involvement within the services.